2015
DOI: 10.1111/mec.13348
|View full text |Cite
|
Sign up to set email alerts
|

Higher genetic diversity in recolonized areas than in refugia of Alnus glutinosa triggered by continent‐wide lineage admixture

Abstract: Genetic admixture is supposed to be an important trigger of species expansions because it can create the potential for selection of genotypes suitable for new climatic conditions. Up until now, however, no continent-wide population genetic study has performed a detailed reconstruction of admixture events during natural species expansions. To fill this gap, we analysed the postglacial history of Alnus glutinosa, a keystone species of European swamp habitats, across its entire distribution range using two molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
62
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(71 citation statements)
references
References 119 publications
6
62
1
2
Order By: Relevance
“…However, Belgium and northern France were represented by only six trees in their study. In contrast, Havrdová et al (2015), using another marker system of cpDNA, revealed the existence of 43 haplotypes on the European scale, of which only one covered the area of our study. Using the same marker system as King and Ferris (1998), we found the same two haplotypes, F and G, in the area concerned.…”
Section: Discussion Genetic Diversity Based On Cpdna Variationmentioning
confidence: 58%
See 1 more Smart Citation
“…However, Belgium and northern France were represented by only six trees in their study. In contrast, Havrdová et al (2015), using another marker system of cpDNA, revealed the existence of 43 haplotypes on the European scale, of which only one covered the area of our study. Using the same marker system as King and Ferris (1998), we found the same two haplotypes, F and G, in the area concerned.…”
Section: Discussion Genetic Diversity Based On Cpdna Variationmentioning
confidence: 58%
“…This model has recently been challenged by a continentwide population genetic study (Havrdová et al 2015), suggesting that multiple refugia served as sources for the postglacial colonization of Europe by A. glutinosa, central Europe being an area of genetic admixture between western and eastern lineages originating from the northern part of the Iberian Peninsula and the Carpathians, respectively. Using SSR markers, Lepais et al (2013) showed a strong distinctiveness of Moroccan populations of A. glutinosa in the rear-edge distribution margins of the species.…”
Section: Communicated By P Ingvarssonmentioning
confidence: 99%
“…Several studies on different organisms (e.g. refs 31,41, 42, 43) have shown that peripheral populations that are migration-dependent may exhibit lower diversity and smaller population sizes than core populations. Therefore, migration-dependent peripheral populations have been shown to be more vulnerable to the detrimental effects of genetic drift (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…STRUCTURE simulations were run, using the admixture model separately with each of correlated allele frequencies and independent allele frequencies (Miao et al, 2013; Havrdová et al, 2015; Zeng et al, 2015), under K -values from 1 to 8. Each simulation had 20 independent repeats, and comprised a burn-in of 500,000 steps followed by 1,500,000 MCMC (Monte Carlo Markov Chain) steps.…”
Section: Methodsmentioning
confidence: 99%